1981
DOI: 10.1073/pnas.78.2.1037
|View full text |Cite
|
Sign up to set email alerts
|

Calcium lability of cytoplasmic microtubules and its modulation by microtubule-associated proteins

Abstract: Detergent-extracted BSC-1 monkey cells have been used as a model system to study the Ca2+ sensitivity of in vivo polymerized microtubules under in vitro conditions. The effects of various experimental treatments were observed by immunofluorescence microscopy. Whereas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
100
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(109 citation statements)
references
References 21 publications
9
100
0
Order By: Relevance
“…Studies in detergentextracted cells showed that microtubules polymerize at low calcium concentrations, whereas increasing calcium concentrations to the micromolar range directly induced microtubule disassembly (Fuller and Brinkley, 1976;Schliwa, 1976). These effects have been hypothesized to be mediated by calcium-dependent regulators of microtubule assembly, such as the abundant neuronal protein calmodulin (Marcum et al, 1978;Schliwa et al, 1981;Lee and Wolff, 1982;Deery et al, 1984). A recent report furthermore suggests that posttranslational modifications that are associated with microtubule stability, such as glutamylation, are regulated by synaptic activity (Maas et al, 2009).…”
Section: Nmda Receptor Activation Suppresses Microtubule Growth In Dementioning
confidence: 99%
“…Studies in detergentextracted cells showed that microtubules polymerize at low calcium concentrations, whereas increasing calcium concentrations to the micromolar range directly induced microtubule disassembly (Fuller and Brinkley, 1976;Schliwa, 1976). These effects have been hypothesized to be mediated by calcium-dependent regulators of microtubule assembly, such as the abundant neuronal protein calmodulin (Marcum et al, 1978;Schliwa et al, 1981;Lee and Wolff, 1982;Deery et al, 1984). A recent report furthermore suggests that posttranslational modifications that are associated with microtubule stability, such as glutamylation, are regulated by synaptic activity (Maas et al, 2009).…”
Section: Nmda Receptor Activation Suppresses Microtubule Growth In Dementioning
confidence: 99%
“…All of the serum-deprived cells within a cell-free zone were microinjected with either the polyclonal or the monoclonal TTL antibodies and incubated for 1-72 h. At that time the cells were rinsed once in warm PHEM buffer (60 mM Pipes, pH 6.95, 25 mM Hepes, 10 mM EGTA, and 2 mM MgCIz) (Schliwa et al, 1981), lysed for I rain with PHEM containing 0.1% (vol/vol) Triton X-100, and then fixed for 20 min in PHEM containing 5 mM EGS. Cells were immunostained with Glu IgG and Tyr IgM antibodies and fluorescein and Texas Red-conjugated secondary antibodies specific for mouse IgG and lgM, respectively.…”
Section: Conversion Kinetics and Ac Tubulin Lmmunostainingmentioning
confidence: 99%
“…Following electrophoresis the gels were fixed for 2 h in 20 % methanol supplemented with 10 % fetal calf serum and 1 mM Bt,cAMP for four days at 37 "C. The coverslips were washed three times with Pipes/Hepes/MgCI,/EGTA buffer (60 mM Pipes, 25 mM Hepes, 2 mM MgCI,, 10 mM EGTA, pH 6.9) and the cells were lysed in this buffer containing 0.2 Brij 58 for 5 min at room temperature [36]. The supernatant was removed and the extracted cells were then fixed with 0.5 glutaraldehyde in Pipes/Hepes/MgCI,/EGTA buffer for 15 min.…”
Section: Antibody Staining Of Proteins Resolved By Electrophoresis Onmentioning
confidence: 99%